Produção forrageira e viabilidade financeira do componente florestal em sistema silvipastoril em pecuária de corte familiar - Jesus, Luana de Campos de (2020)
The implementation of livestock forestry systems in family farming is an option to diversify the use of land to obtain more than one production and another source of income. In this model of land use it is necessary to know the dynamics between the parts composed the system. The aim of this study was to evaluate the native forage production and the financial viability of the forestry component in a livestock forestry systems at a spacing of 3x20 m for multiple use and in rotation for 16 years in family production. Thus forage production, animal load, capacity rate and financial viability were analyzed. To assess forage production, we measured dry mass by double sampling methodology, and accumulation rate by exclusion cages. With the pasture production data it was possible to estimate the animal load and the capacity rate that the system can maintain and to compare the forage production in the sun and shade. For the financial viability analysis, the following appraisal criteria were applied: net present value (NPV), internal rate of return (IRR) and cost benefit ratio (B/C) for a 16 year horizon and the interest rate of 3, 4,5 and 10%. Summer and spring were the seasons with the highest accumulation rates (10,67 Kg ha -1day -1 in january and 3,95 Kg ha -1day -1 in november) and summer and fall were the seasons with the highest forage mass production (2607,41 Kg ha-1 in february and 1624,79 Kg ha-1 in april). The seasons where it is possible to maintain the highest animal load and capacity rate are in summer and fall, 1,46 in february and 1,06 UA/ha in june, and animal load annual average, of 329,77 Kg PV ha-1 dia-1. The forest component in the spacing of 3 x 20 m in single lines and at 4 years of age did not interfere in forage production, due the fact when comparing the accumulation rate in sun and shade there was no difference. For the financial viability analysis criteria the forest component of the system is financially viable, except B/C at the rate of 10%. With NPV greater than zero, IRR exceeding the minimum attractiveness rate, except for the 10% rate for EVL. The forestry component not influence livestock production in the spacing of 3 x 20 m and at 4 years of age In addition that investment in the forest will be financially viable with revenues exceeding costs.